2013
DOI: 10.1371/journal.pone.0073394
|View full text |Cite
|
Sign up to set email alerts
|

European Corn Borer (Ostrinia nubilalis) Induced Responses Enhance Susceptibility in Maize

Abstract: Herbivore-induced plant responses have been widely described following attack on leaves; however, less attention has been paid to analogous local processes that occur in stems. Early studies of maize (Zea mays) responses to stem boring by European corn borer (ECB, Ostrinia nubilalis ) larvae revealed the presence of inducible acidic diterpenoid phytoalexins, termed kauralexins, and increases in the benzoxazinoid 2-hydroxy-4,7-dimethoxy-1,4-benzoxazin-3-one-glucose (HDMBOA-Glc) after 24 h of herbivory. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 86 publications
(131 reference statements)
1
39
0
Order By: Relevance
“…For nutrient poor tissues, increased protein content, even if defense related, could facilitate growth of adapted insects. For example, stem herbivory in maize by the European corn borer (Ostrinia nubilalis) results in elicitation of defense responses, OSderived and frass-derived larval deposition of auxin (indole-3-acetic acid), doubling of protein levels and improved insect growth [32 ]. Thus a combination of wounding, HAMPs and candidate effectors could potentially be used by Lepidoptera larvae to promote plant susceptibility.…”
Section: Os-derived Hamps: Fatty Acid Amino Acid Conjugates (Facs)mentioning
confidence: 99%
“…For nutrient poor tissues, increased protein content, even if defense related, could facilitate growth of adapted insects. For example, stem herbivory in maize by the European corn borer (Ostrinia nubilalis) results in elicitation of defense responses, OSderived and frass-derived larval deposition of auxin (indole-3-acetic acid), doubling of protein levels and improved insect growth [32 ]. Thus a combination of wounding, HAMPs and candidate effectors could potentially be used by Lepidoptera larvae to promote plant susceptibility.…”
Section: Os-derived Hamps: Fatty Acid Amino Acid Conjugates (Facs)mentioning
confidence: 99%
“…Several studies suggest that the auxin indole-3-acetic acid (IAA) also regulates gall formation, since some gall-forming herbivores contain high levels of IAA Davies, 2001a, 2001b;Tooker and de Moraes, 2011a;Straka et al, 2010;Dorchin et al, 2009;Yamaguchi et al, 2012;Tanaka et al, 2013), IAA pools and signaling are enhanced in parasitized plant tissue (Yamaguchi et al, 2012;Tooker and de Moraes, 2011b), and direct application of IAA can result in the formation of gallresembling structures (Hamner and Kraus, 1937;Guiscafrearrillaga, 1949;Schäller, 1968;Bartlett and Connor, 2014;Connor et al, 2012). In the context of chewing insects, however, our understanding is more limited (Dafoe et al, 2013). IAA levels seem to remain unaltered in goldenrod (Solidago altissima) and wheat (Triticum aestivum) attacked by Heliothis virescens caterpillars de Moraes, 2011a, 2011b) and to be reduced in Helicoverpa zea attacked maize (Zea mays; Schmelz et al, 2003) and Manduca sexta-challenged Nicotiana attenuata leaves (Onkokesung et al, 2010;Woldemariam et al, 2012).…”
mentioning
confidence: 99%
“…In maize stems, it was also observed that mechanical damage alone did not result in an increase of JA, but feeding by the Ostrinia nubilalis did (Dafoe et al 2011). This correlated with a higher expression of certain defense-related genes and higher content of defensive compounds in tissue damaged by the Ostrinia nubilalis (Dafoe et al 2011(Dafoe et al , 2013. This would be consistent with the notion that the stems may also receive mechanical damage from the wind and under such circumstances the plant would not want to waste too much energy on induction of defenses in the absence of an insect herbivore or pathogen infection (Howe and Jander 2008).…”
Section: Discussionmentioning
confidence: 94%